American hegemony and the postwar reconstruction of science in Europe - Krige, John (Transformations (M.I.T. Press), 2006)
How the United States used its position as the world's leading scientific and technological power to rebuild European scientific practices and institutions and align them with American interests during the first two decades of the Cold War.